Reproductive justice : the politics of health care for Native American women - Gurr, Barbara Anne (New Brunswick, New Jersey ; London : Rutgers University Press, 2015)
In Reproductive Justice, sociologist Barbara Gurr provides the first analysis of Native American women's reproductive healthcare and offers a sustained consideration of the movement for reproductive justice in the United States. The book examines the reproductive healthcare experiences on Pine Ridge Reservation, home of the Oglala Lakota Nation in South Dakota--where Gurr herself lived for more than a year. Gurr paints an insightful portrait of the Indian Health Service (IHS)--the federal agency tasked with providing culturally appropriate, adequate healthcare to Native Americans--shedding much-needed light on Native American women's efforts to obtain prenatal care, access to contraception, abortion services, and access to care after sexual assault. Reproductive Justice goes beyond this local story to look more broadly at how race, gender, sex, sexuality, class, and nation inform the ways in which the government understands reproductive healthcare and organizes the delivery of this care. It reveals why the basic experience of reproductive healthcare for most Americans is so different--and better--than for Native American women in general, and women in reservation communities particularly. Finally, Gurr outlines the strengths that these communities can bring to the creation of their own reproductive justice, and considers the role of IHS in fostering these strengths as it moves forward in partnership with Native nations.
Introducing our relatives and introducing the story -- Stories from Indian country -- Whose rights? Whose justice? Reproductive oppression, reproductive justice, and the reproductive body -- The ruling relations of reproductive healthcare -- Producing the double discourse : the history and politics of Native-U.S. relations and imperialist medicine -- To uphold the federal government's obligations ... and to honor and protect : the double discourse of the Indian Health Service -- Resistance and accommodation : negotiating prenatal care and childbirth -- One in three : violence against Native women -- Genocidal consequences : contraception, sterilization, and abortion in the fourth world context -- Community knowledges, community capital, and cultural safety -- Conclusions : Native women in the center.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: United States -- Indian Health Service; Indian women -- Health and hygiene -- United States; Reproductive health -- United States; Indians of North America -- Health and hygiene -- United States; Indians of North America; Reproductive rights; Women -- Health and hygiene; Reproductive Health Services -- organization & administration; Healthcare Disparities; Indians, North American; Reproductive Rights; Women's Health; United States; Femmes des Peuples autochtones -- Santé et hygiène -- États-Unis.; Santé de la reproduction -- États-Unis.; Peuples autochtones -- Amérique du Nord; Droits génésiques.; Femmes -- Santé et hygiène.; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; SOCIAL SCIENCE -- Women's Studies; Women -- Health and hygiene; Reproductive rights; Indians of North America; Indian women -- Health and hygiene; Indians of North America -- Health and hygiene; Reproductive health; United States; Electronic books